(untitled) (Research, Society and Development, 2021)
In judging the comfort or discomfort of animals, bioclimatic indices are commonly used. The most used indexes in this type of evaluation are: black globe temperature and humidity index (BGHI), temperature and humidity index (THI), and radiant heat load (RHL), because they are related to physiological and behavioral indicators of the animals. The THI does not absorb the effects of the radiation heat load. For this reason, BGHI and RHL are more suitable for extensive or even confined rearing systems, with high heat load, since they depend on the black globe temperature (BGT), a measure capable of inferring on the homeothermia of the animals. However, most Brazilian weather stations do not have the BGT, which makes it difficult to estimate the amount of heat load to which the animals are exposed. Therefore, the use of meteorological variables to develop equations for estimating the BGT is of great importance in planning actions in different animal production systems. Likewise, the statistical indexes used to evaluate the performance of these estimation equations are essential for their validation. Therefore, this study aimed to perform a review to elucidate bioclimatic indexes, mathematical modeling and statistical indexes for the evaluation of models used to estimate animal thermal comfort.